(untitled) (Journal of the College of Basic Education, 2025)
In this study, we discussed the methodology of Abu Al-Mutarrif Amira Al-Makhzoumi (d. 658 AH - 1259 AD) in his book The History of Mallorca, and the history of the island of Mallorca, which is located on the banks of Andalusia, and the most important historical events that the island was exposed to in that time period of Andalusian history were highlighted. To his style In presenting the historical material and explaining its most important events in a chronological order until the fall of Majorca, this study included two sections. The first section talked about the biography of Abu Amira Al-Makhzoumi, his scientific standing, and his literary works. The second section showed his methodology in his book and how he used Qur’anic verses in mentioning historical facts and his approach in mentioning The cities that witnessed those battles and how to use the historical years, then the conclusion and sources.